The Influence of Company Attributes on Enterprise Risk Management: Mediating Effects of Company Performance - Nadila Nadila (Universitas Internasional Batam, 2024)
The aim of this research is to understand the impact of company attributes (equity, firm age, and firm size) on Enterprise Risk Management in the financial sector by using Company Performance as a mediating variable. The sample for this research consists of companies that have gone public and the amount of data is 470 data from 94 companies over a period of the last 5 years. This research uses a panel data regression method with the help of the eviews 12 and spss 26 software programs to test the influence between variables. The results of this research confirm that company attributes, especially equity, company age, and company size, together have a significant impact on company performance, especially measured by Return on Equity (ROE).